Teleoperação de cadeira de rodas robótica com controlador de atraso de tempo - Couto, Eduardo Henrique Montenegro (2017)
The present work evaluates a PD-Like and impedance controller applied to a teleoperated robotic wheelchair with visual feedback from a camera. This evaluation considers thedelay influence ondata and image transmission in the system. The force feedback imposed by the controller was initially applied to a robot, emulating a wheelchair to test the algorithms, to the joystick, relating the difference between master and slave, and based on measurements of a laser sensor to detect presence of possible obstacleson the way. The system was implemented and tested in a real wheelchair.The time to complete the proposed tasks, the robot synchronism error, and the spatial error regarding the trajectory and the specified path were analysed. In addition, user EEG signals were collected in order to measure the user's level of attention during the task, which was correlated with the completed NASA-TLX questionnaire shortly after the conclusion of the protocol. A satisfactory behaviour of the controller and execution of thetask by the user was observed, and that the level of attention increases with the presence of time delay.